The optimal parameters of agricultural insurance of the products in the Ukraine - Trusova, Natalia; Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Rubtsova, Natalia; Рубцова, Наталя Миколаївна; Рубцова, Наталья Николаевна; Rubtsov, Mykola; Chkan, Iryna; Чкан, Ірина Олександрівна; Чкан, Ирина Александровна; Radchenko, Natalia; Радченко, Наталя Миколаївна; et al. (My University, 2021)
EN : The article deals with the complex indicative forecasting of agricultural insurance parameters, which have approximate empirical dependences of variables and provide approximation of actuarial calculations of the franchise, in order to optimize the rates of insurance compensation for losses in agricultural production. The tools for minimizing the risks of agricultural production are substantiated. The typology of instruments for regulating the risks of agricultural production by transferring their risk distribution in the institutional environment and market infrastructure is studied. It is proved that vertical integration has a positive effect of compensation for losses of agricultural production, taking into account alternative diversification combinations with actual variables and the occurrence of a certain insurance event. Multicriteria optimization of the parameters of partial distribution of risks of agricultural production, which simultaneously provide the maximum possible value of the expected return with a minimum value of the risk of the portfolio of assets of agricultural enterprises, is fulfilled. The utility function for accidental consequences in agricultural insurance is substantiated, as it guarantees the effective indicator of income at variable values of uncertainty. Approximate empirical dependences of variables are determined, which provide approximation of actuarial calculations of the franchise, in order to optimize the rates of insurance indemnity in agricultural production. Models of indicative forecasting of optimal parameters of agricultural insurance on the market of agricultural products of Ukraine on insurance payments and insurance premiums, which have a decreasing function, have been developed; insured sum and franchise have dynamic fluctuations.
Los parámetros óptimos del seguro agrícola de los productos en Ucrania
Keywords: risks; insurance indemnity; insurance premium; franchise; market; riesgos; indemnización del seguro; franquicia; mercado